Bahasa Inggris - Desy Novita Sari; Rahmi Rahmi (Paradigma - Jurnal Komputer dan Informatika, 2023)
Although there is a lot of research on websites, there is very little research on art gallery websites in Indonesia. As a result, this study examines the quality of the National Gallery of Indonesia’s (commonly referred to as Galnas) website as a source providing information about the gallery by analyzing end-user perceptions through methods such as WebQual 4.0, importance–performance analysis, and customer satisfaction index (CSI). Fifty undergraduate and postgraduate college students in the Library and Information Science (LIS) program of the Faculty of Humanities at the University of Indonesia were selected as respondents based on convenience sampling. The study found that compared to other sources of information, the Galnas website was chosen the least, but the overall services of the website met user expectations, as evidenced by a CSI score of 83.88% for undergraduate college students and a CSI score of 74.96% for postgraduate college students. This research contributes to the enhancement of the quality and accessibility of the Galnas website.